A Longitudinal Description of Emergency Medical Services Professionals by Race/Ethnicity. (28th November 2016) - Crowe, Remle P.; Levine, Roger; Eggerichs, Jennifer J.; Bentley, Melissa A.
Abstract: Objective: The objective of this paper was to compare demographics, employment variables, satisfaction, and motivation for entering the field of Emergency Medical Services (EMS) between members of under-represented races/ethnicities and members of the majority group. Methods: A cohort of nationally certified EMS professionals was followed for 10 years through annual surveys; however, race/ethnicity was only available for 9 years (2000-2008). Descriptive statistics and 95% confidence intervals (CIs) were calculated and significance was determined by lack of CI overlap. Results: From 2000 through 2008, the range of proportions of nationally certified EMS professionals by race/ethnicity was as follows: whites: 83.5%-86.0%, Hispanics: 4.2%-5.9%, and African-Americans: 2.5%-4.6%. There were no significant changes in the proportion of minority EMS professionals over the study period. Hispanics and African-Americans combined increased slightly from 6.7% of the population in 2000 to 9.9% in 2008. Likewise, the proportion of all under-represented races/ethnicities increased slightly from 2000 (14.0%) to 2008 (16.5%). Females were under-represented in all years. Nationally certified African-Americans were significantly more likely to be certified at the Emergency Medical Technician (EMT)-Basic level (compared with the EMT-Paramedic level) than whites in all but one survey year. The proportion of Hispanics registered at the EMT-Basic level was significantly higher than whites in three survey years. Accordingly, a larger proportion of whites were nationally registered at the EMT-Paramedic level than both African-Americans and Hispanics. A significantly larger proportion of African-Americans reported working in urban communities (population >25, 000) compared with whites for nine of the 10 survey years. Similarly, a significantly larger proportion of Hispanics worked in urban communities compared with whites in 2002 and from 2005 to 2008. For satisfaction measures, there were no consistent differences between races/ethnicities. Among factors for entering EMS, the proportion of whites who reported having a friend or family member in the field was significantly higher than African-Americans in all years and significantly higher than Hispanics in four of the nine years. Conclusion: The ethnic/racial diversity of the population of nationally certified EMS professionals is not representative of the population served and has not improved over the 2000-2008 period. Similar to other health care professions, Hispanics and African-Americans are under-represented in EMS compared with the US population. This study serves as a baseline to examine under-represented populations in EMS. RP Crowe, R Levine, JJ Eggerichs, MA Bentley .A longitudinal description of Emergency Medical Services professionals by race/ethnicity .Prehosp Disaster Med .2016 ;31 (Suppl.1 ):s30 –s69 .